Behavior Characteristics of Argon Bubbles on Inner Surface of Upper Tundish Nozzle during Argon Blowing Process - Yang Li (Metals, 2018)
During continuous casting of aluminum-killed steel, clogging of tundish nozzle frequently occurs, which seriously disrupts the normal casting sequences and deteriorates strand quality. Generally, argon blowing technology in the form of a stable and continuous argon film on the inner surface of the upper nozzle is employed to prevent the upper nozzle from clogging in the production. To explore the formation mechanism and influence factors of this argon film, a water model of the upper nozzle with blowing argon with a similarity ratio of 1:1 was built. The results show that the number of bubble chains increases gradually with increasing argon flow rate and casting speed, and the argon gas curtain appears at the bottom half of the upper nozzle. For a given argon flow rate, the velocity of argon gas bubbles increased gradually with increasing casting speed, and decreased gradually with increasing distance from the upper nozzle top. For a given casting speed, the average velocity of argon gas bubbles was largest at a distance from the upper nozzle top of 6 mm with argon flow rate of 150 L/h. The results could provide theoretical and technical basis for the optimization of blowing argon parameters in order to prevent the clogging of upper nozzle and improve strand quality.